Wind Load Analysis on Temporary Scaffolding Structures in High-Altitude Venues Based on Numerical Simulation: A Case Study From the 2022 Beijing Olympics - Ming-hong Sun; Lei Zhang; Xu-yang Li; Xiao-guang Li; Qing-wen Li (Advances in Civil Engineering)
Scaffolding is widely used in construction, maintenance, and other activities as a temporary support structure. However, strong winds frequently cause scaffolding structures to collapse. Thus, the influence of wind load on the performance of such temporary support systems cannot be ignored. During the 2022 Beijing Winter Olympics, the scaffolding at the National Alpine Skiing Center in Yanqing District faced challenges from high-altitude winds. This study evaluated its performance under a wind speed of 33 m/s using ANSYS Workbench. The result show that the maximum wind speed of Model A is 55 m/s, which occurs at the connection between the channel plate and the stand plate. And the maximum wind speeds of Model B and Model C are 47 m/s and 43 m/s, respectively, which both occur at the top of the stand. Compared with Model A and Model B, the wind pressure, stress, and displacement of Model C are larger, in which the negative pressure of Model C is below −3600 Pa and the positive pressure is above 600 Pa at the position of the connection between the stand plate and the rod. The stress at the connection between the channel plate and the stand plate is more than three times of that of the other positions of the plate, and the displacement of the stand plate can reach 68 mm in some areas. Therefore, optimizing the connection part, considering local wind direction when arranging, and placing windproof measures can all reduce the impact of strong winds on the scaffolding.